A study of prevalence of low back pain among workers of Dunham-Bush Industries Sdn. Bhd. Kajang Selangor, 1998 - Jasbeer Singh; Noor Hassim Ismail (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross sectional study was conducted to determine the prevalence of low back pain and its risk factors among workers of Dunham Bush Industries Sdn. Bhd. Kajang Selangor. A total of 145 workers participated in the study by self administered questionnaire. It was found from this study that the prevalence of low back pain among workers was 42.1%. Majority of the workers who complained of low back pain were Malays 54.4%. There was a statistical difference of low back pain between Malays and non Malay workers, (P<0.05). Among the workers who had low back pain a total of 42.2%, works overtime always, and a total of 45.7% works overtime sometimes. However there was no significant relationship between prevalence of low back pain and age and also length of service (P>0.05). A total of 79.0% of workers who had low back pain are in the opinion that the low back pain is due to factors related to work. Components of physical disturbance such as shoulder pain, difficulty in breathing, giddiness and other musculoskeletal pain increased, compared before and after work. Time motion studies revealed that workers stand 38.4% , bend their body 34.2%, and only sits (8.3%), through out working hours. Time budget studies of workers shows, workers work about 11 hours 30 minutes per day. Tasks performed by workers that can cause low back pain were identified and suggestions to reduced and prevent were discussed.